Pengembangan Buku Teks Berbasis Pembelajaran Saintifik Pada Mata Pelajaran Akuntansi Perbankan Syariah Untuk Kelas XI Kompetensi Perbankan Syariah SMK - Luqman Hakim; Hariyati; Yafi, Muhammad Fahmi (Universitas Pendidikan Ganesha, 2022)
This development research produces textbooks using scientific steps at the core learning activities. The purpose of this study is to analyze the process of developing textbooks, analyze the feasibility of textbooks, and analyze students' responses to textbooks based on scientific approaches on the subjects of accounting of Islamic banking. The type of research used is Research and Development (R&D) with the 4D development model developed by Thiagarajan without doing the disseminate stage. The subjects of this study were students of class XI Islamic Banking at SMK Negeri 1 Lamongan. The results of this study show the average results of the feasibility of textbooks as determined by experts to be 85.34 percent in the very valid category. The content feasibility component shows a result of 86.15 percent with a very valid category, the presentation feasibility component is at 82% with a very valid category, linguistic component is at 100% with a very valid category, and the graphics component is at 99.57 percent with a very valid category. The results of product trials also show that textbooks can attract students' interest in learning, as indicated by the percentage of 87.87% with valid categories.